On propagation of rayleigh type surface wave in five different theories of thermoelasticity - Singh, Baljeet; Verma, Shailja (Zielona Góra: Uniwersytet Zielonogórski)
The governing equations for a homogeneous and isotropic thermoelastic medium are formulated in the context of coupled thermoelasticity, Lord and Shulman theory of generalized thermoelasticity with one relaxation time, Green and Lindsay theory of generalized thermoelasticity with two relaxation times, Green and Nagdhi theory of thermoelasticity without energy dissipation and Chandrasekharaiah and Tzou theory of thermoelasticity.
Keywords: generalized thermoelasticity; surface waves; Rayleigh wave; frequency equation